2020
DOI: 10.1007/s12020-020-02381-7
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide ACE (I/D) polymorphism may affect COVID-19 recovery rate: an ecological meta-regression

Abstract: With the emergence of the Novel Coronavirus (2019-nCoV), researchers worldwide have started detecting the probable pathogenesis of the disease. The renin-angiotensin system (RAS) and angiotensin-converting enzymes have received a good deal of attention as possible pathways involved in 2019-nCoV pathogenesis. As the experiments seeking to find potential medications acting on these pathways are being conducted in the early phases, having an ecological worldview on the relationship between the prevalence of COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 16 publications
4
71
0
Order By: Relevance
“…With interest with read the paper by Hatami et al on angiotensin converting enzyme 1 (ACE1) I/D polymorphism and the recovery rate in COVID-19. Although we agree that genetics play a role in COVID-19 prevalence and mortality [ 1 3 ], we disagree with various aspects (quality and representativity of the genotype distribution studies enroled, some epidemiological data) of the statistical analysis, which has been carried out in the paper.…”
mentioning
confidence: 84%
“…With interest with read the paper by Hatami et al on angiotensin converting enzyme 1 (ACE1) I/D polymorphism and the recovery rate in COVID-19. Although we agree that genetics play a role in COVID-19 prevalence and mortality [ 1 3 ], we disagree with various aspects (quality and representativity of the genotype distribution studies enroled, some epidemiological data) of the statistical analysis, which has been carried out in the paper.…”
mentioning
confidence: 84%
“…ACE2 expression is less frequent in patients with SARS-CoV. Genetic polymorphism may explain why COVID-19 has the highest incidence rate in Europe than in Africa [ [62] , [63] , [64] , [65] ].…”
Section: Genetic Polymorphism Of Acementioning
confidence: 99%
“…As discussed earlier, ACE2 is the receptor for SARS-CoV-2. It has been reported that the involvement of ACE2 receptors is also related to the renin-angiotensin system (RAS) in 2019-nCoV pathogenesis [63]. Very recently, a meta-analysis was conducted to get insight into the relationship between the prevalence of COVID-19 disease and the genetic differences in the genes involved in the RAS system [63].…”
Section: Pathogenesismentioning
confidence: 99%
“…It has been reported that the involvement of ACE2 receptors is also related to the renin-angiotensin system (RAS) in 2019-nCoV pathogenesis [63]. Very recently, a meta-analysis was conducted to get insight into the relationship between the prevalence of COVID-19 disease and the genetic differences in the genes involved in the RAS system [63]. The results of the study suggest that the increase of the I/D allele frequency ratio significantly increases the recovery rate (point estimate: 0.48, confidence interval (CI) 95%: 0.05-0.91, p = 0.027), but the I/D allele frequency ratio has no significant difference in the case of death rate (point estimate: 1.74, CI 95%: 4.5-1.04, p = 0.22).…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation